Different SNP combinations in the GCH1 gene and use of labor analgesia - Sundström-Poromaa Inger; Nyberg Fred; Grönbladh Alfhild; Dabo Fatimah; Åkerud Helena (SAGE Publishing, 2010)
Abstract Background The aim of this study was to investigate if there is an association between different SNP combinations in the guanosine triphosphate cyclohydrolase (GCH1) gene and a number of pain behavior related outcomes during labor. A population-based sample of pregnant women (n = 814) was recruited at gestational week 18. A plasma sample was collected from each subject. Genotyping was performed and three single nucleotide polymorphisms (SNP) previously defined as a pain-protective SNP combination of GCH1 were used. Results Homozygous carriers of the pain-protective SNP combination of GCH1 arrived to the delivery ward with a more advanced stage of cervical dilation compared to heterozygous carriers and non-carriers. However, homozygous carriers more often used second line labor analgesia compared to the others. Conclusion The pain-protective SNP combination of GCH1 may be of importance in the limited number of homozygous carriers during the initial dilation of cervix but upon arrival at the delivery unit these women are more inclined to use second line labor analgesia.